Pengaruh Keaktifan Berorganisasi dan Pengalaman Magang Terhadap Kesiapan Kerja Mahasiswa FEB UNJ Angkatan 2021 - Adelia Salsabila; Henry Eryanto; Rizki Firdausi Rachmadania (Indo Publishing, 2025)
This study aims to analyze the influence of organizational activity and internship experience on the work readiness of students at the Faculty of Economics and Business, Jakarta State University. The research method used in this study is a survey method with a quantitative approach. The population in this study were all 906 students of the Faculty of Economics and Business, Jakarta State University, class of 2021. The sampling technique used Proportionate Random Sampling using the Slovin formula with a margin of error of 5%, resulting in a sample of 277 students. The data analysis technique used in this study was SmartPLS software version 4.0. The data analysis techniques used consisted of inner model analysis and inner model analysis. The results of the calculation of X1 against Y show that the Original Sample score is 0.500 and the T-Statistic is 7.743 > 1.96 and the P-Value is 0.000 < 0.05. For X2 versus Y, the Original Sample score was 0.494, the T-Statistic was 7.199 > 1.96, and the P-Value was 0.000 < 0.05. The F^2 calculation for variable X1 versus Y yielded an F^2 score of 0.713, and for variable X2 versus Y, an F^2 score of 0.697. Therefore, this study concludes that Organizational Activity and Internship Experience simultaneously have a positive and significant effect on students' Job Readiness.